Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/4398469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Semirigid Ankle Brace on the In Vivo Kinematics of Patients with Functional Ankle Instability during the Stance Phase of Walking

Abstract: An ankle brace is commonly used by patients after they suffer from initial ankle sprains, reducing the incidents of recurrent sprain or limiting laxity in joints with functional ankle instability (FAI). However, whether the application of a semirigid ankle brace can improve the abnormal ankle gait kinematics of patients with FAI remains unknown. This study aimed to determine the effect of a semirigid ankle brace on the gait kinematics of ankle joints through 3D-2D fluoroscopy image registration. A total of 8 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…We found that wearing ankle braces decreased the maximum inversion angle of the subtalar joint during landing. This finding was consistent with that of a previous DFIS study ( Zhang et al, 2019 ). showed that a semirigid ankle brace could significantly limit the eversion-inversion ROM of the tibiotalar and subtalar joints during walking.…”
Section: Discussionsupporting
confidence: 94%
“…We found that wearing ankle braces decreased the maximum inversion angle of the subtalar joint during landing. This finding was consistent with that of a previous DFIS study ( Zhang et al, 2019 ). showed that a semirigid ankle brace could significantly limit the eversion-inversion ROM of the tibiotalar and subtalar joints during walking.…”
Section: Discussionsupporting
confidence: 94%
“…7-9 In addition, a recent study investigating the effect of a semirigid ankle brace on in vivo kinematics during the stance phase of walking in patients with functional ankle instability found normalization and alteration of the subtalar and talocrural movements in opposite directions. 57…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In addition, a recent study investigating the effect of a semirigid ankle brace on in vivo kinematics during the stance phase of walking in patients with functional ankle instability found normalization and alteration of the subtalar and talocrural movements in opposite directions. 57 Despite the results of studies that suggested a positive effect of ankle taping or braces on proprioception, a recent meta-analysis found no evidence that ankle orthoses or taping affected proprioceptive acuity in participants with CAI. 49 Other mechanisms such as decreased mechanical instability or improved confidence during functional tasks may thus contribute to balance improvements when ankle braces or taping are used.…”
Section: Discussionmentioning
confidence: 99%
“…DFIS studies have also found that ankle braces can limit the IN/EV of the tibiotalar and subtalar joints during the stance phase of walking ( Zhang et al, 2019 ). However, ankle braces neither limit anterior translation and the PF of the subtalar joints nor help the RoM of the subtalar joints return to a normal or near-normal level in patients with LAS and CAI ( Cao et al, 2019b ).…”
Section: Dual Fluoroscopic Imaging System Studies On Pathological Populationsmentioning
confidence: 99%